A proposed model for text and image encryption using different ‎techniques - Shihab A. Shawkat‎‎; Israa Al-Barazanchi (Universitas Ahmad Dahlan, 2022)
Data security and protection is one of the most common technologies used in the field of computer ‎science. This is because of its great importance in all fields related to daily life, whether political, ‎economic, and other aspects change. In this research paper, a new intelligent system ‎that ‎concentrates on image ‎and text encryption and decryption is proposed. ‎Furthermore, ‎the image recognition rate is increased. In this paper, ‎the Rivest Shamir Adleman 3 key (RSA3k) algorithm is used but ‎in a new ‎technique to encrypt and decrypt ‎text. The proposed technique relies on using square root ‎of public ‎key as ‎private key. XOR ‎operation for colored images ‎encryption and decryption is ‎performed. By calculating signal to noise ratio (PSNR), mean square error (MSE), and bit error ‎rate (BER), the most important things that we address how to provide data security ‎for large data based on encryption techniques and increase the security of multimedia data and texture date and ‎address the problem of time and accuracy in image matching. ‎the results show that the quality of images after decryption is good.